2005
DOI: 10.1002/anie.200500342
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Riboflavin Receptor Prepared by a Template Analogue Imprinting Strategy

Abstract: Molecular imprinting has resulted in a range of robust polymer-based receptors that are being considered for use in a variety of applications based on molecular recognition. [1] The technique entails polymerization of mono-and polyfunctional monomers in the presence of a template, whose subsequent removal leaves sites that can be reoccupied by the template or a closely related compound. These synthetic receptors are distinguished by their robustness and ease of synthesis, but they also have drawbacks, notably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 19 publications
3
48
0
2
Order By: Relevance
“…The design of imprinted polymers for tegafur presented here was based on our prior experience in the development of recognition elements for uracil derivatives, which contain a hydrogen bond acceptordonor-acceptor (A-D-A) imide moiety [10,11]. Our previous work, as well as that of others' [12][13][14][15], has shown that polymerisable functional monomers with complementary donor-acceptor-donor (D-A-D) arrays result in highly selective imprinted polymers, capable of recognising the template substance even in the presence of strongly competing analytes.…”
Section: Introductionmentioning
confidence: 99%
“…The design of imprinted polymers for tegafur presented here was based on our prior experience in the development of recognition elements for uracil derivatives, which contain a hydrogen bond acceptordonor-acceptor (A-D-A) imide moiety [10,11]. Our previous work, as well as that of others' [12][13][14][15], has shown that polymerisable functional monomers with complementary donor-acceptor-donor (D-A-D) arrays result in highly selective imprinted polymers, capable of recognising the template substance even in the presence of strongly competing analytes.…”
Section: Introductionmentioning
confidence: 99%
“…Water may interfere with hydrogen bonds involved in the recognition and MIPs relying on non-covalent interactions to the template are therefore often prepared in aprotic organic media. Optimal rebinding is usually observed in similar aprotic organic solvents as the ones used during the imprinting, although several cases of successful rebinding in aqueous media have been reported [8,[16][17][18][19][20][21][22][23][24][25]. The pH and the ionic strength of the rebinding solvent mixture have been recognized as parameters affecting the binding capacity [16,19,26].…”
Section: Introductionmentioning
confidence: 99%
“…Such materials have been shown to outperform their biological counterparts in real sample applications, as they are capable of retaining their function in environments that fall outside of normal physiological conditions e.g. extremes temperatures and pH values [19].…”
Section: In 2000 Rachkov and Minoura Demonstrated What Ismentioning
confidence: 99%